The Role Of Magnetic Resonance Spectroscopy To Improve The Accuracy Of Brain Tumor Diagnosis - Arisetijono, Eko; Pradhana, Satwika; Yueniwati, Yuyun (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2024)
Background: In Indonesia, primary brain tumor incidence reaches 7 per 100,000, with a mortality rate of 4.25 per 100,000 people per year. Histopathology is the gold standard for determining tumor type and degree of aggressiveness. Non-invasive approaches and precision in determining brain tumor grading are essential for management, avoiding less necessary surgical procedures and challenging cases, one of which is MR Spectroscopy. Purpose: To analyze the relationship between Cho/Cr and Cho/NAA's suitability ratio in MRS and the degree of malignancy in histopathology and investigate the influence of differences in Cho/Cr, Cho/NAA ratio, and lactate lipid peaks in MRS on the degree of malignancy in histopathology in primary brain tumors. Methods: We retrospectively reviewed 17 patients with high and low-grade brain tumors using an observational study with a cross-sectional study design. We measured the Cho/Cr and Cho/NAA ratios and identified the Lipid Lactate peak on the homogenous contrast enhancement area with the highest Cho area. We conducted data analysis using McNemar's test and independent t- test. Result: Statistical analysis showed no significant difference in the ratio of Cho/Cr, Cho/NAA, and lactate lipids (p > 0.05), and this study obtained the suitability of the MRS indicator with histopathological results in Cho/NAA with p = 0.219 (p > 0.05) with an accuracy of 65%. Conclusion: The Cho/NAA ratio's conformity in determining the degree of brain tumor compared to histopathological results with an accuracy of 65%. Further research with a larger sample is necessary for the results to be more optimal